Religious discourse in newspaper «Kazakh» - Ахметбекова А.,, А.; Қажынова М., М. (Journal of Oriental Studies, 2017)
The article discusses the “Kazakh” newspaper, which was published in the 1913-1916 years. In the early 20th century intellectualls Kazakh people took an active part in determining the content of religious articles, topics that had been identified by internal factors. Through the theme “Kazak” article authors try to determine the characteristics of the religious discourse and to review the articles that are focused on reform ideas.